Studi Kelayakan Bisnis Pelumas Food Grade Petro-Canada untuk Industri Makanan dan Minuman di Jawa Timur - Jeffri Sucipto Utomo; Felecia - (Jurnal Titra, 2014)
This research is conducted to analize business feasibility study of food grade lubricants Petro-Canada brand for food and beverages industries in East Java. The number of medium large scale industries in Indonesia which engaged in processing food and beverage is 5.865 in 2012. East Java has 1906 food and beverage industries that needs 605.270 liters lubricats per year. Business feasibility study is analyzed using market analysis, technical analysis, legal analysis, and financial analysis. Data collection technique for market analysis is using questionnaire which was distributed to 25 food and beverages processing industries located in Surabaya and surrounding areas. Technical analysis showed the working system, business location, and company management. It is also supported by legality aspect of the law in business activities. The business requires initial investment of Rp 5.558.855.000, and will reach break even point in 21 months with 3 years internal rate of return up to 67%. Based on these analysis Petro-Canada food grad lubricants for food and beverage industries in East Java is feasible.